2020
DOI: 10.5194/wes-2020-66
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the scaling of wind turbine rotors

Abstract: Abstract. This article formulates laws for scaling wind turbine rotors. Although the analysis is general, the article primarily focuses on subscaling, i.e. on the design of a smaller size model mimicking a full-scale machine. The present study considers both the steady-state and transient response cases, including the effects of aerodynamic, elastic, inertial and gravitational forces. The analysis reveals the changes to physical characteristics induced by a generic change of scale, indicates which characterist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Given a set of ambient wind conditions, the FLORIS model computes the steady-state flow within a wind farm and, in turn, the power output of the individual turbines (Doekemeijer et al, 2019). The present results were obtained with the MATLAB implementation available online (Doekemeijer and Storm, 2018), using the selfSimilar velocity deficit, the rans deflection, the wake model of Bastankhah and Porté-Agel (2016), the quadraticRotorVelocity wake combination, and the crespoHernandez added turbulence (Crespo and Hernández, 1996). To improve accuracy at the cost of a slightly increased computational effort, the power of a turbine is computed by integrating the flow at the rotor disk using P = 1/2ρ A V 3 C P dA (where ρ is air density, V the local wind speed, and A the rotor disk area), instead of the original implementation based on the rotor-average wind speed.…”
Section: Floris Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a set of ambient wind conditions, the FLORIS model computes the steady-state flow within a wind farm and, in turn, the power output of the individual turbines (Doekemeijer et al, 2019). The present results were obtained with the MATLAB implementation available online (Doekemeijer and Storm, 2018), using the selfSimilar velocity deficit, the rans deflection, the wake model of Bastankhah and Porté-Agel (2016), the quadraticRotorVelocity wake combination, and the crespoHernandez added turbulence (Crespo and Hernández, 1996). To improve accuracy at the cost of a slightly increased computational effort, the power of a turbine is computed by integrating the flow at the rotor disk using P = 1/2ρ A V 3 C P dA (where ρ is air density, V the local wind speed, and A the rotor disk area), instead of the original implementation based on the rotor-average wind speed.…”
Section: Floris Modelmentioning
confidence: 99%
“…The ambient wind field in the model is horizontally sheared to match the wind tunnel inflow. The model was tuned based on wake measurements of one isolated G1 turbine, as discussed in Campagnolo et al (2019), obtaining the parameters reported in Table 1; notice that, having been tuned with ad hoc measurements, the values of these parameters differ from the ones provided by Bastankhah and Porté-Agel (2016) and Crespo and Hernández (1996). The wind speed at y = 0 was set to 5.25 m s −1 , while the turbulence intensity was set to 6.1 %.…”
Section: Floris Modelmentioning
confidence: 99%
“…Quantities referred to the scaled model are indicated with the subscript (•) M , while quantities referred to the full-scale physical system with the subscript (•) P . Scaling is defined by two parameters (Bottasso and Campagnolo, 2020;Canet et al, 2020): the length scale factor n l = l M /l P , where l is a characteristic length (for example the rotor radius R), and the time compression ratio n t = t M /t P , where t is time. In the present case n l = 1/162.1 and n t = 1/82.5.…”
Section: Scalingmentioning
confidence: 99%
“…-Detailed flow measurements are possible with a plethora of devices, from standard pressure and hot-wire probes, to PIV (Meinhart, 1999) and scanning lidars (van Dooren et al, 2017), whereas measurements of comparable accuracy are today hardly possible at full scale. Additionally, time flows faster in a scaled experiment than at full scale (Bottasso and Campagnolo, 2020;Canet et al, 2020;Campagnolo et al, 2020), which means that a large informational content can be accumulated over relatively short periods of time. small-scale model blade compared to a full-scale machine implies very different aerodynamic characteristics of the airfoils, which in turn drive a number of specific design choices of the scaled model (Bottasso and Campagnolo, 2020;Canet et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation